The city of Kash in Transoxiana, a study of its economic and cultural ‎conditions (55 AH/674 AD - 653 AH/1255 AD)‎ - Alaa Mutar Taieh (مجلة جامعة الأنبار للعلوم الإنسانية, 2024)
Aims: The research aims to study the city of Kash and identifies its political and cultural conditions under  the Arab-Islamic rule. The study also aimed to listing the most important Arab-Islamic campaigns that contributed to the conquest of the city, and then identifying the status of the city politically and scientifically.Methodology: In presenting the events of the topic, the study adopted the well-thought-out research plan, in which we followed the methodology of thematic presentation, as within these topics we followed another approach, which is the historical presentation of the sequence of events. The timeframe for the research began from the year (55 AH/674 AD), which is the date that represents the entry of the first vanguard of the conquering Arab armies into the city, and ends to the year (653 AH/1255 AD).Results: After analyzing the materials of the study, the results showed that the city of Kash is one of the cities of Transoxiana located in the Islamic East. It is a bustling and populated city. It was conquered by Muslim Arabs in the year (55 AH/674 AD), then it was re-conquered by Commander Qutaybah bin Muslim al-Bahili in the year (91 AH/709 AD). The study also showed that the city's general conditions stabilized and it became part of The Arab Islamic state. The city was administered by the rulers of Transoxiana, as the men of the Abbasid mission took it as their shelter and a starting point for spreading their ideas to mobilize people against the Umayyad rule. Al-Muqnad Al-Khorasani also used it as his military headquarters after he fortified himself in its castle (Bisman). Kash witnessed a great scientific movement, as many scholars appeared in it who excelled in various sciences, the forefront of which were Hadith, jurisprudence, interpretation, language, literature, and history. The city fell at the hands of the Mongols in the year 653 AH/1255 AD.Conclusions: it can be concluded that the city of Kash canot be considered to be one of the major cities of Transoxiana, like Bukhara, Samarkand, and Khwarezm, but it is considered one of the cities of the second generation of Transoxiana in terms of political, cultural, and economic importance, just like the city of Nasf .